Mapping somatosensory connectivity in adult mice using diffusion MRI tractography and super-resolution track density imaging - Richards, K; Calamante, F; Tournier, J-D; Kurniawan, ND; Sadeghian, F; Retchford, AR; Jones, GD; Reid, CA; Reutens, DC; Ordidge, R; Connelly, A; Petrou, S (Elsevier, 2014)
In this study we combined ultra-high field diffusion MRI fiber tracking and super-resolution track density imaging (TDI) to map the relay locations and connectivity of the somatosensory pathway in paraformaldehyde fixed, C57Bl/6J mouse brains. Super-resolution TDI was used to achieve 20 μm isotropic resolution to inform the 3D topography of the relay locations including thalamic barreloids and brainstem barrelettes, not described previously using MRI methodology. TDI-guided mapping results for thalamo-cortical connectivity were consistent with thalamo-cortical projections labeled using virus mediated fluorescent protein expression. Trigemino-thalamic TDI connectivity maps were concordant with results obtained using anterograde dye tracing from brainstem to thalamus. Importantly, TDI mapping overcame the constraint of tissue distortion observed in mechanically sectioned tissue, enabling 3D reconstruction and long-range connectivity data. In conclusion, our results showed that diffusion micro-imaging at ultra-high field MRI revealed the stereotypical pattern of somatosensory connectivity and is a valuable tool to complement histologic methods, achieving 3D spatial preservation of whole brain networks for characterization in mouse models of human disease.